513. Effectiveness of Pulsed Xenon Ultraviolet Light Disinfection System to Decrease Clostridium difficile Infections at the South Texas Veterans Health Care System. (26th November 2018) - Cepeda, Victor; Cadena, Jose; Reveles, Kelly R; Dickerson, Charmayne
Abstract: Background: Clostridium difficile is the leading pathogen implicated in healthcare-associated infections. C. difficile spores can survive for months on surfaces, allowing for transmission between patients; thus, environmental disinfection is a cornerstone for C. difficile infection (CDI) prevention. Pulsed xenon ultraviolet (PX-UV) light disinfection effectively eliminates C. difficile spores from surfaces and can be used as an adjunct to manual cleaning; however, few studies have evaluated the effects of this technology on healthcare facility-onset CDI (HO-CDI) rates. The objective of this study was to compare HO-CDI rates prior to and post-implementation of PX-UV disinfection in an acute care hospital. Methods: This was a quasi-experimental study in the South Texas Veterans Health Care System (STVHCS), San Antonio, Texas from 2011 to 2018. The PX-UV system was implemented beginning January 1, 2013. HO-CDI rates were calculated as CDI cases per 10, 000 patient-days. Rates were compared between the pre-PX-UV period (2011–2012) and post-PX-UV period (2013–2018) using the conditional maximum likelihood estimate of rate ratio. The association between number of beds cleaned and HO-CDI incidence was evaluated using Pearson correlation. Results: During the 2-year preintervention period, the HO-CDI rate was 9.09 per 10, 000 patient-days compared with 9.44 per 10, 000 patient days in the postintervention period (RR 1.038; 95% CI 0.817 – 1.328) ( P = 0.7703). HO-CDI rates peaked in 2015 (13.60 per 10, 000) and declined steadily thereafter through 2018 (6.86 per 10, 000). There was not a significant correlation between number of beds cleaned and HO-CDI incidence (R=0.3713; 95% CI −0.0597–0.6856; P = 0.0889). Conclusion: PX-UV disinfection did not significantly reduce HO-CDI rates in the first 5 years of use; however, more recent data demonstrate HO-CDI rates lower than that of the preintervention period. Disclosures: All authors: No reported disclosures.